Pandangan Snouck Hurgronje Terhadap Tradisi Pembacaan Kitab Hadis di Nusantara Pada Akhir Abad Ke-19 - Ahmad Firdaus; M. Khoirul Huda (Prophetica: Journal of Hadith Studies, 2025)
This article examines the views of Christiaan Snouck Hurgronje, the prominent Dutch Orientalist and colonial advisor, on the hadith text Ḥāsyiyah ʿalā Mukhtaṣar Ibnu Abī Jamrah li al-Bukhārī, as expressed in his official advisory letter (halaman 1989–1991 of Ambtelijke Adviezen van C. Snouck Hurgronje) to the Dutch colonial government on 28 April 1891. Using critical discourse analysis (CDA) based on Teun A. Van Dijk's three-dimensional model—text, social cognition, and social analysis—the study analyzes the textual strategies, cognitive schemas, and power dynamics embedded in Snouck's advisory memo regarding the practice of reading this hadith collection among Acehnese Muslims during the Dutch-Aceh War. Contrary to his earlier skepticism about hadith authenticity expressed in Muhammadanisme, and against the colonial government's initial suspicion that this reading practice was a vehicle for anti-colonial resistance, Snouck assessed the kitab positively, argued it posed no political threat, and recommended its preservation in the Bataviaasch Genootschap library. The analysis reveals that Snouck's positive framing was shaped by his Islam Politiek framework, his dual identity as scholar and colonial advisor, and his extensive immersive knowledge of Islam acquired through fieldwork in Mecca and across the Dutch East Indies. Each of Van Dijk's thirteen textual elements—from lexicon and metaphor to presupposition and coherence—converges on a single discursive goal: reframing the colonial government's suspicious gaze toward an act of Islamic piety as something that poses no threat to colonial authority. The article argues that Snouck's treatment of this hadith text represents a notable case study in the complex, non-deterministic relationship between Orientalist scholarship, colonial administration, and Islamic textual tradition.